Why Awe Promotes Prosocial Behaviors? The Mediating Effects of Future Time Perspective and Self-Transcendence Meaning of Life - Li, Jing-Jing; Dou, Kai; Wang, Yu-Jie; Nie, Yan-Gang (Frontiers in Psychology, 2019)
Awe is an emotion experience when individuals encounter with such powerful stimulate beyond their own understanding. Guided by conceptual analysis of awe as a trait positive emotion, we tested the hypothesis that dispositional awe results in an improvement of individual's self-transcendence meaning of life (STML) and affects future time perspective, and increase prosocial behavior. Mediational data demonstrate that the effects of awe on prosociality are explained, by improving STML self and future time perspective. These findings indicate that awe may help situate individuals within broader social contexts and enhance collective concern.